Vitamin E reduces endosulfan-induced toxic effects on morphology and behavior in early development of zebrafish (Danio rerio). (March 2017) - Dale, K.; Rasinger, J.D.; Thorstensen, K.L.; Penglase, S.; Ellingsen, S.
Abstract: The aim of this study was to investigate if vitamin E (α-TOC) modulates the developmental toxicity of the pesticide endosulfan (ESF), using a modified zebrafish embryotoxicity test (ZET). Zebrafish ( Danio rerio ) embryos were exposed from 6 to 72 h post fertilization (hpf) to either ESF (0.1–50 mg/L) or α-TOC (0.01–3 mM) alone or in combination. The effects of these exposures on embryonic morphology, larval behavior and antioxidant gene expression were analyzed. Phenotypic analysis at 48 hpf showed that ESF led to a dose-dependent increase in embryonic deformities, including axis malformations, pericardial edema and reduced pigmentation. Co-exposure of ESF with α-TOC (1–3 mM) significantly ( p  < 0.05) reduced ESF-induced embryonic malformations. Exposure to solely α-TOC did not affect rates of survival or malformations. Behavior studies showed that ESF caused hyperactivity at 5 days post fertilization, indicating a developmental neurotoxic effect. The ESF-induced hyperactivity was ameliorated by α-TOC. Elevated ESF concentrations caused down-regulation of the antioxidant genes cuzn-sod, gpx1a and cat, suggesting that ESF promoted oxidative stress in the embryos. α-TOC did not prevent the ESF-induced dysregulation of these genes. These results demonstrate that α-TOC protects against phenotypic and behavioral effects caused by ESF but did not rescue ESF-induced aberrations in antioxidant gene expression. Highlights: Endosulfan exposure in zebrafish embryos causes neurodevelopmental toxicity in a dose-responsive manner. Vitamin E can reduce endosulfan induced hyperactivity in zebrafish embryos. Morphological malformations caused by endosulfan exposure in zebrafish embryos are alleviated by vitamin E.